DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BEI - Annisafitri Shafarini; Lilik Farida; Tatok Endhiarto; Ahmad Ahsin Kusuma Mawardi; Almas Farah Dinna Dewi (VALUE: Journal of Business Studies, 2022)
This research aims to determine and analyze the factors that influence the firm value either directly or indirectly through the capital structure of the consumer goods industry sector companies listed on the Indonesia Stock Exchange. The secondary data used in this research are from annual report of the consumer goods industry sector companies within 2016 – 2020 period. The analytical method use Path Analysis. The population in this reseacrh consisted consumer goods industry sector companies listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling technique and obtained as many as 19 companies according to the criteria. The test results show that profitability and dividend policy have a significant effect on the capital structure and firm value, firm size has no significant effect on the capital structure and firm value. Capital Structure can mediating the effect of profitability on firm value, but can not mediating the effect of firm size and dividend policy on firm value.